Strategi Komunikasi Pemasaran Berbasis Kearifan Lokal untuk Memajukan Desa Wisata: Studi Kasus Kampung Wisata Keranggan - Estriana, Virna; Pratami, Rezki; Adhvidya, Adhvidya (Syntax Literate, 2025)
This study aims to explore the implementation of marketing communication based on local wisdom in Kampung Wisata Keranggan, identify the challenges encountered, and determine optimization strategies to enhance tourist attraction. Utilizing a phenomenological qualitative approach, this research analyzes in-depth interviews with village tourism managers, local communities, tourists, and representatives of local government. Additionally, it employs the Integrated Marketing Communication (IMC) theory as a framework to understand the consistency of messages conveyed through various communication channels. The findings reveal that communication approaches based on local wisdom, such as the promotion of traditional dances, handicrafts, and folklore, have successfully created an authentic image and attracted tourists. However, several challenges affect the effectiveness of these strategies, including limited funding, insufficient digital marketing skills, and inadequate access to technology. Moreover, inconsistencies in the scheduling of cultural activities pose significant challenges. To improve the effectiveness of marketing communication, the recommended optimization strategies include diversifying promotional content, enhancing the quality of digital infrastructure, providing marketing training for local communities, and strengthening collaboration with external stakeholders. By implementing these measures, Kampung Wisata Keranggan can fortify its position as a competitive and sustainable cultural tourism destination. This study is expected to provide practical contributions to the development of marketing communication strategies based on local wisdom and serve as an academic reference for further research in tourism marketing.